Case reportsTherapeutic effects of CO2 laser therapy of linear nevus sebaceous in the course of the Schimmelpenning-Feuerstein-Mims syndrome - Kiedrowicz, Magdalena; Kacalak-Rzepka, Anna; Królicki, Andrzej; Maleszka, Romuald; Bielecka-Grzela, Stanisława (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
The Schimmelpenning-Feuerstein-Mims (SFM) syndrome is a rare phakomatosis which comprises a nevus sebaceous of Jadassohn, seizures and developmental delay associated with a wide spectrum of extracutaneous abnormalities including neurological, skeletal, ocular, cardiovascular and urogenital defects. We are presenting a case of an 18-year-old patient with systemic features of the SFM syndrome and an extensive linear nevus sebaceous partially removed with a carbon dioxide (CO2) laser. The treatment options of skin lesions in patients with SFM are discussed.